Precise healing of oral and maxillofacial wounds: tissue engineering strategies and their associated mechanisms - Zhao, Qingtong; Leng, Changyun; Lau, Manting; Choi, Kawai; Wang, Ruimin; Zeng, Yuyu; Chen, Taiying; Zhang, Canyu; Li, Zejian (Frontiers in Bioengineering and Biotechnology, 2024)
Precise healing of wounds in the oral and maxillofacial regions is usually achieved by targeting the entire healing process. The rich blood circulation in the oral and maxillofacial regions promotes the rapid healing of wounds through the action of various growth factors. Correspondingly, their tissue engineering can aid in preventing wound infections, accelerate angiogenesis, and enhance the proliferation and migration of tissue cells during wound healing. Recent years, have witnessed an increase in the number of researchers focusing on tissue engineering, particularly for precise wound healing. In this context, hydrogels, which possess a soft viscoelastic nature and demonstrate exceptional biocompatibility and biodegradability, have emerged as the current research hotspot. Additionally, nanofibers, films, and foam sponges have been explored as some of the most viable materials for wound healing, with noted advantages and drawbacks. Accordingly, future research is highly likely to explore the application of these materials harboring enhanced mechanical properties, reduced susceptibility to external mechanical disturbances, and commendable water absorption and non-expansion attributes, for superior wound healing.